Increasing the energy efficiency of filtering concentrate at a mining enterprise - Starykh Svetlana; Okorokov Anton; Rastorguev Anton; Taranenko Maxim; Ermolaev Denis (E3S Web of Conferences)
The study on improving the accuracy of process control is based on the process of filtering concentrate of the beneficiation plant of a mining enterprise. To fully reflect the importance of the study, it is necessary to identify the shortcomings of the current level of the automated process control system and the possibility of automatic data transfer by the enterprise personnel. The study is based on the principle of microwave moisture metering methodology on the finished product conveyors of the filtration section. It is assumed that the efficiency of the process will be achieved by installing moisture meters on the finished product conveyors, which are based on the flow moisture meters. The implementation of this project will systematize the provision of process personnel with timely information on the current moisture of the final concentrate for timely management decisions on managing the filtration technology as a whole, as well as increase production efficiency by reducing the specific energy consumption of the enterprise.